A high performance NiCoCrAlY bond coat manufactured using laser powder deposition. (September 2017) - Luo, Lirong; Shan, Xiao; Zou, Zhonghua; Zhao, Chunshan; Wang, Xin; Zhang, Aiping; Zhao, Xiaofeng; Guo, Fangwei; Xiao, Ping
Graphical abstract: Highlights: We developed a laser powder deposition method to fabricate MCrAlY bond coat. MCrAlY Bond coat deposited by laser powder deposition shows excellent oxidation resistance over that deposited by air plasma spray and high velocity air fuel. MCrAlY Bond coat deposited by laser powder deposition forms a pure, adherent alumina with a lower growth rate. No mixed oxides were formed on MCrAlY bond coat deposited by laser powder deposition. Oxidation resistance was attributed to the dense, uniform coating structure. Abstract: A high performance NiCoCrAlY bond coat with dense dendritic microstructure was fabricated using laser powder deposition (LPD) technique. The thermally grown oxides (TGO) formed on the coating deposited by laser powder deposition is predominantly alumina instead of the mix oxides usually formed on the coatings prepared by air plasma spray and high velocity air fuel. Isothermal oxidation tests performed at 1150 °C reveal that the LPD bond coat shows significantly better spallation resistance and lower TGO growth rate. The superior spallation resistance of the TGO is further discussed in relation to the unique microstructure of the LPD bond coat.